Evaluation of different antiparasitic molecules in captive mammals at Rabat Zoo, Maroc - Yahya Taki; Safae Annouri; Maria Bourquia (Medicamentul Veterinar, 2022)
At the Rabat zoological garden, 30 species belonging to 5 mammalian orders were investigated for the prevalence of gastrointestinal and pulmonary parasites by fecal analysis, and the prevalence rate was found to be 70%, with 21 species revealed infected. To optimize the therapeutic protocol in Rabat Zoo, an evaluation of the commercialized antiparasitic molecules was performed by treating 19 out of 21 positive species with Fenbendazole, Pyrantel, Mebendazole, Ivermectin, and Toltrazuril. To determine the therapeutic efficacy of the molecules used, fecal samples from each treated species were collected on the 7th-day post-treatment. Of the 19 species treated, 15 were found to be negative after the treatment, showing a 78.95% efficacy of the molecules. Drug efficacy according to mammalian order was distributed as follows: 66.66% in Artiodactyla, 100% in Perissodactyla and Primates, and 83.33% in Carnivora. In conclusion, the present study confirms that the antiparasitic structure currently available in Morocco are effective against most of the gastrointestinal parasites encountered in African wild mammals.